All Days 2014
DOI: 10.4043/24851-ms
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Containment Assurance Program - Key Element Overview and Best Practice Examples

Abstract: The goal of Subsurface Containment Assurance is to ensure that no environmental damage, damage to operated assets, or impacts on well operations (drilling or production) are incurred by leakage of production or injection fluids from their intended zones. Subsurface Containment Assurance involves the integrated efforts of the subsurface (reservoir and overburden characterization), the wells (planning, construction, well integrity and abandonment) and the operations (process and well operations and management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Analysis discussed above has shown that induced fractures that connect with highpermeability structures, such as adjacent wells, are a potential pathway for the contamination of groundwater or the ground surface. Clearly, to avoid problems with leakage along these types of structures, careful characterization of the system is necessary to identify any wells or geologic features within the area expected to be affected by the well stimulation treatment (Shultz et al, 2014). Bachu and Valencia (2014) recommend conducting hydraulic fracturing from offset wells at a safe distance, which is not specified, but would need to be evaluated using fracture modeling and field experience.…”
Section: Best Practices For Well Drilling Construction Stimulation and Monitoring Methodsmentioning
confidence: 99%
“…Analysis discussed above has shown that induced fractures that connect with highpermeability structures, such as adjacent wells, are a potential pathway for the contamination of groundwater or the ground surface. Clearly, to avoid problems with leakage along these types of structures, careful characterization of the system is necessary to identify any wells or geologic features within the area expected to be affected by the well stimulation treatment (Shultz et al, 2014). Bachu and Valencia (2014) recommend conducting hydraulic fracturing from offset wells at a safe distance, which is not specified, but would need to be evaluated using fracture modeling and field experience.…”
Section: Best Practices For Well Drilling Construction Stimulation and Monitoring Methodsmentioning
confidence: 99%
“…One may claim that the subject of subsurface containment assurance fulfills the well integrity requirements, however, in fact it is more comprehensive than the well integrity. It includes well integrity, subsurface integrity, and any aspect of deepwater and surface facilities which are directly relevant to upstream exploration, production, and abandonment operations [25]. As an example the well integrity of abandoned wells or fields might be influenced by nearby injector wells influencing the pressure regime.…”
Section: Containment Assurance Of the Abandoned Wells Or Fieldsmentioning
confidence: 99%